PENDIDIKAN KARAKTER DI MADRASAH SALAFIYAH - Fihris Sa’adah (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2011)
Theoretically, one of the dominant factors that influence the development of individual character are environmental factors which is a condition that allows the process of personal character development. Creating an conducive environment to the development of character Girikusumo Salaf Islamic School students is done by creating a tradition /habituation practical in everyday life in all their daily activities in relation to the quality of their religious or otherwise. Attempt the formation of character through this Salaf Islamic school in addition to the above character education, can also be done simultaneously through the educational value of the following steps. First, apply a “modeling” or “exemplary” or “uswah hasanah”. Second, efforts to explain or clarify to students constantly about the value of good and evil has been done in the Girikusumo Salaf Islamic School. Third, implement the SIS is based on character education.